Preparation process of tin-free environment-friendly polyester resin

By using bismuth catalyst and tris(2-hydroxyethyl)benzene-1,3,5-tricarboxylate, the environmental pollution and biohazard problems caused by the use of organotin catalysts during the preparation process of existing polyester resins are solved, and the high heat resistance and biodegradation properties of polyester resins are achieved.

CN119505210AActive Publication Date: 2025-02-25ANHUI YOCHON NEW MATERIALS TECHNOLOGY CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510059396.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-02-25
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The organic tin catalyst used in the preparation process of existing polyester resins can cause environmental pollution and biohazards, and its thermal stability and biodegradation performance are insufficient.

Method used

A bismuth catalyst such as bismuth isocitate and 4-dimethylaminopyridine are used to form a composite catalyst, instead of the traditional organotin catalyst, and tris(2-hydroxyethyl)benzene-1,3,5-tricarboxylate is added to the esterification polycondensation reaction to improve the glass transition temperature and biodegradation properties of the polyester resin.

Benefits of technology

The prepared environmentally friendly polyester resin without tin has good heat resistance, biodegradability and environmental protection properties, reduces environmental pollution and meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of polyester resin, and discloses a preparation process of tin-free environment-friendly polyester resin, which is characterized in that dihydric alcohol, dibasic acid, a catalyst, an antioxidant, an acidolysis agent, a curing accelerator and the like are reacted to obtain the tin-free environment-friendly polyester resin. According to the invention, bismuth iso-octoate and 4-dimethylaminopyridine form a compound catalyst to replace a traditional organic tin catalyst, so that the tin-free environment-friendly polyester resin is obtained, and the blank of the tin-free environment-friendly polyester resin is filled. The toxic and side effects are effectively reduced, the environmental pollution is reduced, and the requirements of environment-friendly polyester resin are met. Meanwhile, tris (2-hydroxyethyl) benzene-1, 3, 5-triformate is added to participate in esterification polycondensation reaction, contains a plurality of hydroxyl crosslinking polymerization sites and a heat-resistant benzene ring structure, and is crosslinked into polyester resin molecules, so that the glass-transition temperature, the heat stability and the biodegradability of the resin can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyester resins, in particular to a preparation process of a tin-free and environment-friendly polyester resin. Background Art

[0002] At present, polyester resins for powder coatings mainly use titanium or organotin compounds as catalysts for esterification reactions, among which titanium catalysts have the disadvantages of being easily hydrolyzed, having poor stability, and having a long reaction time when preparing polyester resins. After the organotin catalyst participates in the catalytic reaction, it will remain in the polyester resin permanently, and will gradually precipitate onto the resin surface over time. The organotin catalyst will have a mutagenic effect on the environment and organisms, and has caused considerable harm to the human body and the environment. In order to curb pollution, many countries in the world have formulated corresponding laws and regulations to restrict or prohibit the use of organotin compounds in different fields. A method for controlling the melt index of biodegradable polyester is disclosed in a Chinese invention patent with a publication number of CN115304751B, wherein potassium carbonate, sodium metasilicate, zinc isooctanoate, bismuth isooctanoate, etc. are used as catalysts for ester exchange reactions, and the prepared biodegradable polyester material has an adjustable melt index effect. However, the patent does not improve the glass transition temperature, thermal stability, and biodegradable properties of the polyester resin. Summary of the invention

[0003] The invention provides a preparation process of a tin-free, environment-friendly polyester resin with good heat resistance and excellent biodegradability.

[0004] Technical solution: A preparation process of a tin-free and environment-friendly polyester resin, comprising: adding a diol, a dibasic acid, a catalyst, and an antioxidant into a reaction kettle, introducing nitrogen, heating while stirring, and reacting at 165-175°C for 1-1.5 hours; evacuating to control the vacuum degree to 10-20Pa, heating to 235-245°C, reacting for 4-6 hours, discharging water generated by the esterification reaction, and when the acid value reaches 11-16 mgKOH / g, reducing the temperature to 215-225°C, adding an acidolysis agent, and reacting at the temperature; when the acid value reaches 40-44 mgKOH / g, heating to 230-235°C, evacuating to control the vacuum degree to 10-20Pa, and reacting at the temperature; when the acid value reaches 33-38 mgKOH / g, adding a curing accelerator; cooling, discharging, and obtaining a tin-free and environment-friendly polyester resin.

[0005] Preferably, the acidolysis agent is any one or a combination of isophthalic acid or tris(2-hydroxyethyl)benzene-1,3,5-tricarboxylate.

[0006] Preferably, the catalyst is one or a combination of bismuth isooctanoate, bismuth laurate, bismuth cycloalkaneate, and 4-dimethylaminopyridine.

[0007] Preferably, the amount of diol is 38-42 parts by weight, the dibasic acid is 60-68 parts by weight, the antioxidant is 0.5-0.6 parts by weight, the catalyst is 0.3-0.45 parts by weight, the acidolysis agent is 16-20 parts by weight, and the onium salt curing accelerator is 0.1-0.12 parts by weight.

[0008] Preferably, the diol is neopentyl glycol. The dibasic acid is any one or a combination of terephthalic acid or 2,5-furandicarboxylic acid.

[0009] Preferably, the antioxidant is any one or a combination of hindered phenol antioxidants and phosphite antioxidants. The curing accelerator is triphenylethylphosphonium bromide.

[0010] Technical effect: The present invention uses bismuth catalysts such as bismuth isooctanoate and 4-dimethylaminopyridine to form a composite catalyst to replace the traditional organic tin catalyst to obtain a tin-free environmentally friendly polyester resin, filling the gap of tin-free environmentally friendly polyester resin. The synthetic raw materials do not contain tin-containing raw materials such as organic tin catalysts, which effectively reduces toxic side effects and environmental pollution, and meets the requirements of environmentally friendly polyester resins.

[0011] The polyester resin prepared by the present invention has good and moderate acid value and viscosity, and is light in color. At the same time, tris (2-hydroxyethyl) benzene-1,3,5-tricarboxylate is added to participate in the esterification polycondensation reaction, which contains multiple hydroxyl cross-linking polymerization sites and a heat-resistant benzene ring structure, which is cross-linked into the polyester resin molecule, and can improve the glass transition temperature and thermal stability of the resin.

[0012] The tris(2-hydroxyethyl)benzene-1,3,5-tricarboxylate of the present invention contains three ester groups, and multiple hydroxyl groups react with dibasic acid to generate ester groups, thereby increasing the ester group content of the polyester resin, which is beneficial to improving the biodegradability of the polyester resin. Moreover, the tris(2-hydroxyethyl)benzene-1,3,5-tricarboxylate is cross-linked to the polyester resin molecular chain. When the three ester groups of the tris(2-hydroxyethyl)benzene-1,3,5-tricarboxylate are degraded, the cross-linked molecular chain of the polyester resin can be destroyed, and the degradation rate of the polyester resin is accelerated, thereby showing a higher biodegradation rate. DETAILED DESCRIPTION

[0013] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0014] Tris(2-hydroxyethyl)benzene-1,3,5-tricarboxylate was prepared according to the method of Angew. Chem. Int. Ed. 2004, 43, 1360-1363, "Absolute Helical Arrangement of Stacked Benzene Rings: Heterogeneous Double-Helical Interaction Comprising a Hydrogen-Bonding Belt and an Offset Parallel Aromatic-Aromatic Interaction Array" (DOI No. 10.1002 / anie.200352788). The structural formula is: .

[0015] Embodiment 1:

[0016] 38g neopentyl glycol, 55g terephthalic acid, 10g 2.5-furandicarboxylic acid, 0.1g catalyst bismuth isooctanoate, 0.3g catalyst 4-dimethylaminopyridine, 0.3g hindered phenol antioxidant 1076, 0.23g phosphite antioxidant 168 were added to the reactor, nitrogen was introduced, the temperature was raised while stirring, and the reaction was carried out at 165°C for 1.5h; the vacuum degree was controlled at 20Pa, the temperature was raised to 240°C, and the reaction was carried out for 6h, and the water generated by the esterification reaction was discharged. When the acid value reached 16 mgKOH / g, the temperature was reduced to 225°C, 14g acidolysis agent isophthalic acid and 2g tris (2-hydroxyethyl) benzene-1,3,5-tricarboxylate were added, and the reaction was kept warm; when the acid value reached 40mgKOH / g, the temperature was raised to 235°C, the vacuum degree was controlled at 20Pa, and the reaction was kept warm; when the acid value reached 33 When the content of triphenylethylphosphonium bromide is about 0.1g, the curing accelerator is added; the temperature is lowered, and the material is discharged to obtain a tin-free and environmentally friendly polyester resin.

[0017] Embodiment 2:

[0018] 42g neopentyl glycol, 55g terephthalic acid or 13g 2.5-furandicarboxylic acid, 0.1g catalyst bismuth laurate, 0.2g catalyst 4-dimethylaminopyridine, 0.33g hindered phenol antioxidant 1076, 0.27g phosphite antioxidant 168 were added to the reactor, nitrogen was introduced, the temperature was raised while stirring, and the reaction was carried out at 165°C for 1.5h; the vacuum degree was controlled at 20Pa, the temperature was raised to 245°C, and the reaction was carried out for 4h, and the water generated by the esterification reaction was discharged. When the acid value reached 11 mgKOH / g, the temperature was reduced to 220°C, 14g acidolysis agent isophthalic acid and 3g tris (2-hydroxyethyl) benzene-1,3,5-tricarboxylate were added, and the reaction was kept warm; when the acid value reached 44mgKOH / g, the temperature was raised to 230°C, the vacuum degree was controlled at 20Pa, and the reaction was kept warm; when the acid value reached 33 When the content of triphenylethylphosphonium bromide is about 0.12g, a curing accelerator is added; the temperature is lowered, and the material is discharged to obtain a tin-free and environmentally friendly polyester resin.

[0019] Embodiment 3:

[0020] 40g neopentyl glycol, 52g terephthalic acid or 11g 2.5-furandicarboxylic acid, 0.1g catalyst bismuth cyclohexane acid, 0.35g catalyst 4-dimethylaminopyridine, 0.28g hindered phenol antioxidant 1076, 0.22g phosphite antioxidant 168 were added to the reactor, nitrogen was introduced, the temperature was raised while stirring, and the reaction was carried out at 175°C for 1h; the vacuum degree was controlled at 10Pa, the temperature was raised to 235°C, and the reaction was carried out for 6h, and the water generated by the esterification reaction was discharged. When the acid value reached 16 mgKOH / g, the temperature was reduced to 215°C, 14g acidolysis agent isophthalic acid and 4g tris (2-hydroxyethyl) benzene-1,3,5-tricarboxylate were added, and the reaction was kept warm; when the acid value reached 40mgKOH / g, the temperature was raised to 230°C, the vacuum degree was controlled at 10Pa, and the reaction was kept warm. When the acid value reached 33 When the content of triphenylethylphosphonium bromide is about 0.12g, a curing accelerator is added; the temperature is lowered, and the material is discharged to obtain a tin-free and environmentally friendly polyester resin.

[0021] Embodiment 4:

[0022] 38g neopentyl glycol, 50g terephthalic acid or 11g 2.5-furandicarboxylic acid, 0.1g catalyst bismuth isooctanoate, 0.28g catalyst 4-dimethylaminopyridine, 0.3g hindered phenol antioxidant 1076, 0.27g phosphite antioxidant 168 were added to the reactor, nitrogen was introduced, the temperature was raised while stirring, and the reaction was carried out at 170°C for 1.5h; the vacuum degree was controlled at 20Pa, the temperature was raised to 245°C, and the reaction was carried out for 4h, and the water generated by the esterification reaction was discharged. When the acid value reached 11 mgKOH / g, the temperature was reduced to 225°C, 14g acidolysis agent isophthalic acid and 5g tris (2-hydroxyethyl) benzene-1,3,5-tricarboxylate were added, and the reaction was kept warm; when the acid value reached 44mgKOH / g, the temperature was raised to 230°C, the vacuum degree was controlled at 20Pa, and the reaction was kept warm. When the acid value reached 38 When the content of triphenylethylphosphonium bromide is about 0.1g, the curing accelerator is added; the temperature is lowered, and the material is discharged to obtain a tin-free and environmentally friendly polyester resin.

[0023] Embodiment 5:

[0024] 40g neopentyl glycol, 53g terephthalic acid or 12g 2.5-furandicarboxylic acid, 0.1g catalyst bismuth isooctanoate, 0.25g catalyst 4-dimethylaminopyridine, 0.3g hindered phenol antioxidant 1076, 0.22g phosphite antioxidant 168 were added to the reactor, nitrogen was introduced, the temperature was raised while stirring, and the reaction was carried out at 170°C for 1.5h; the vacuum degree was controlled at 20Pa, the temperature was raised to 240°C, the reaction was carried out for 4h, the water generated by the esterification reaction was discharged, and when the acid value reached 11 mgKOH / g, the temperature was reduced to 215°C, 14g acidolysis agent isophthalic acid and 6g tris (2-hydroxyethyl) benzene-1,3,5-tricarboxylate were added, and the reaction was kept warm; when the acid value reached 40mgKOH / g, the temperature was raised to 230°C, the vacuum degree was controlled at 20Pa, the reaction was kept warm, and when the acid value reached 33 When the content of triphenylethylphosphonium bromide is about 0.1g, the curing accelerator is added; the temperature is lowered, and the material is discharged to obtain a tin-free and environmentally friendly polyester resin.

[0025] Comparative Example 1:

[0026] 38g neopentyl glycol, 55g terephthalic acid, 10g 2.5-furandicarboxylic acid, 0.4g catalyst monobutyl tin oxide, 0.3g hindered phenol antioxidant 1076, 0.23g phosphite antioxidant 168 were added to the reactor, nitrogen was introduced, the temperature was raised while stirring, and the reaction was carried out at 165°C for 1.5h; the vacuum degree was controlled at 20Pa, the temperature was raised to 240°C, and the reaction was carried out for 6h, and the water generated by the esterification reaction was discharged. When the acid value reached 16 mgKOH / g, the temperature was reduced to 225°C, 14g acidolysis agent isophthalic acid and 2g tris (2-hydroxyethyl) benzene-1,3,5-tricarboxylate were added, and the reaction was kept warm; when the acid value reached 40 mgKOH / g, the temperature was raised to 235°C, the vacuum degree was controlled at 20Pa, and the reaction was kept warm; when the acid value reached 33 When the content of triphenylethylphosphonium bromide is about 0.1g, the curing accelerator is added; the temperature is lowered, and the material is discharged to obtain a tin-free and environmentally friendly polyester resin.

[0027] Comparative Example 2:

[0028] 38g neopentyl glycol, 55g terephthalic acid, 10g 2.5-furandicarboxylic acid, 0.1g catalyst bismuth isooctanoate, 0.3g catalyst 4-dimethylaminopyridine, 0.3g hindered phenol antioxidant 1076, 0.23g phosphite antioxidant 168 were added to the reactor, nitrogen was introduced, the temperature was raised while stirring, and the reaction was carried out at 165°C for 1.5h; the vacuum degree was controlled at 20Pa, the temperature was raised to 240°C, and the reaction was carried out for 6h, and the water generated by the esterification reaction was discharged. When the acid value reached 16 mgKOH / g, the temperature was reduced to 225°C, 14g acidolysis agent isophthalic acid was added, and the reaction was kept warm; when the acid value reached 40 mgKOH / g, the temperature was raised to 235°C, the vacuum degree was controlled at 20Pa, and the reaction was kept warm; when the acid value reached 33 When the content of triphenylethylphosphonium bromide is about 0.1g, the curing accelerator is added; the temperature is lowered, and the material is discharged to obtain a tin-free and environmentally friendly polyester resin.

[0029] Comparative Example 3:

[0030] 38g neopentyl glycol, 55g terephthalic acid, 10g 2.5-furandicarboxylic acid, 0.1g catalyst bismuth isooctanoate, 0.3g catalyst 4-dimethylaminopyridine, 0.3g hindered phenol antioxidant 1076, 0.23g phosphite antioxidant 168 were added to the reactor, nitrogen was introduced, the temperature was raised while stirring, and the reaction was carried out at 165°C for 1.5h; the vacuum degree was controlled at 20Pa, the temperature was raised to 240°C, and the reaction was carried out for 6h, and the water generated by the esterification reaction was discharged. When the acid value reached 16 mgKOH / g, the temperature was reduced to 225°C, 14g acidolysis agent isophthalic acid and 2g trimethylolpropane were added, and the reaction was kept warm; when the acid value reached 40 mgKOH / g, the temperature was raised to 235°C, the vacuum degree was controlled at 20Pa, and the reaction was kept warm. When the acid value reached 33 When the content of triphenylethylphosphonium bromide is about 0.1g, the curing accelerator is added; the temperature is lowered, and the material is discharged to obtain a tin-free and environmentally friendly polyester resin.

[0031] Observe the appearance color of the polyester resin.

[0032] Refer to GB / T 6743-2008 standard to test the acid value of polyester resin.

[0033] The viscosity of the polyester resin was tested using a viscometer with the temperature set at 200°C. After the temperature stabilized, a polyester resin sample was taken and placed in the center of the test table of the viscometer for viscosity measurement.

[0034] The polyester sample was tested by differential scanning calorimetry. 10 mg of polyester resin sample was weighed and placed on the stage. After setting the parameters in the program, DSC measurement was performed. The measurement temperature range was 25-100°C and the heating rate was 10°C / min. The test results are shown in Table 1.

[0035] Table 1 Polyester resin performance test

[0036] After testing, each embodiment uses bismuth catalysts such as bismuth isooctanoate and 4-dimethylaminopyridine to form a composite catalyst, and the prepared polyester resin has a good and moderate acid value and viscosity, and the color is lighter, showing grayish white. At the same time, the glass transition temperature reaches 67.5-75.1°C, and the heat resistance is good. This is mainly because tris (2-hydroxyethyl) benzene-1,3,5-tricarboxylate contains multiple hydroxyl polymerization sites and a heat-resistant benzene ring structure, which is cross-linked to the polyester resin molecule, which can improve the glass transition temperature and thermal stability of the resin.

[0037] In Comparative Example 1, monobutyltin oxide was used as a catalyst, and the obtained polyester resin was darker in color and light yellow.

[0038] Comparative Example 2 did not add tris(2-hydroxyethyl)benzene-1,3,5-tricarboxylate, and Comparative Example 3 added trimethylolpropane. Both had lower glass transition temperatures and thermal stability.

[0039] According to the national standard GB / T 19277-2003, the biodegradability of polyester resin was tested by composting method. The test results are shown in Table 2.

[0040] Table 2 Degradation performance test

[0041] After testing, compared with Comparative Examples 2 and 3, Examples 1-5 added tris(2-hydroxyethyl)benzene-1,3,5-tricarboxylate, and the prepared polyester resin has a higher biodegradation rate and biodegradability, mainly because tris(2-hydroxyethyl)benzene-1,3,5-tricarboxylate itself contains three ester groups, and multiple hydroxyl groups react with dibasic acids to generate ester groups, thereby increasing the ester group content of the polyester resin, which is beneficial to improving the biodegradability of the polyester resin, and tris(2-hydroxyethyl)benzene-1,3,5-tricarboxylate is cross-linked to the polyester resin molecular chain. When its three ester groups are degraded, the cross-linked molecular chains of the polyester resin can be destroyed, accelerating the degradation rate of the polyester resin, thereby showing a higher biodegradability.

Claims

1. A process for preparing a tin-free environmentally friendly polyester resin, characterized in that: The preparation process comprises: adding diol, dibasic acid, catalyst and antioxidant into a reaction kettle, introducing nitrogen, stirring and heating, reacting at 165-175°C for 1-1.5h; vacuumizing, heating to 235-245°C, reacting for 4-6h, discharging water generated by esterification reaction, when the acid value reaches 11-16 mgKOH / g, reducing the temperature to 215-225°C, adding acidolysis agent and keeping the temperature for reaction; when the acid value reaches 40-44 mgKOH / g, heating to 230-235°C, vacuumizing, keeping the temperature for reaction, when the acid value reaches 33-38 mgKOH / g, adding curing accelerator; cooling, discharging, and obtaining tin-free environmentally friendly polyester resin; The acidolysis agent is any one or a combination of isophthalic acid or tris(2-hydroxyethyl)benzene-1,3,5-tricarboxylate; The catalyst is one or a combination of bismuth isooctanoate, bismuth laurate, bismuth cyclohexaneate and 4-dimethylaminopyridine.

2. The process for preparing the tin-free environmentally friendly polyester resin according to claim 1, characterized in that: The dosage of the diol is 38-42 parts by weight, the dibasic acid is 60-68 parts by weight, the antioxidant is 0.5-0.6 parts by weight, the catalyst is 0.3-0.45 parts by weight, the acidolysis agent is 16-20 parts by weight, and the onium salt curing accelerator is 0.1-0.12 parts by weight.

3. The process for preparing the tin-free environment-friendly polyester resin according to claim 1, characterized in that: The diol is neopentyl glycol.

4. The process for preparing the tin-free environment-friendly polyester resin according to claim 1, characterized in that: The dibasic acid is any one or a combination of terephthalic acid or 2,5-furandicarboxylic acid.

5. The process for preparing the tin-free environment-friendly polyester resin according to claim 1, characterized in that: The antioxidant is any one or a combination of hindered phenol antioxidants and phosphite antioxidants.

6. The process for preparing the tin-free environment-friendly polyester resin according to claim 1, characterized in that: The curing accelerator is triphenylethylphosphonium bromide.

7. The process for preparing the tin-free environment-friendly polyester resin according to claim 1, characterized in that: The vacuum degree of the vacuum pumping is controlled to be 10-20Pa.

Citation Information

Patent Citations

  • A method for controllably adjusting the melt index of biodegradable polyester

    CN115304751B

  • Method for preparing light stabilizer 622

    CN104592504A

  • Preparation method of polyester polyol

    CN107987257A

  • Polyester resin for high-weather-resistance low-temperature TGIC cured powder coating and preparation method thereof

    CN111533892A

  • Method for controllably adjusting melt index of biodegradable polyester

    CN115304751A